PERSEPSI PETANI PADI SAWAH TERHADAP TEKNOLOGI PERTANIAN DI DESA TATENGESAN KECAMATAN PUSOMAEN KABUPATEN MINAHASA TENGGARA (Perceptions of Rice Farmers on Agricultural Technology in Tatengesan Village, Pusomaen Sub District, Southeast Minahasa Regency) - Ovrits Brayen Lontaan; Jenny Baroleh; Leonardus R. Rengkung (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to determine the perception of rice farmers on agricultural technology in Tatengesan Village, Pusomaen Sub District, Southeast Minahasa Regency. This research was conducted from March to April 2021. The data collected in this study were primary data obtained from direct interviews with lowland rice farmers using a questionnaire. Secondary data were obtained from the Tatengesan Village Office, Sub District Seed Center Office, Regency Agriculture Service and data related to researches taken from the internet. Sampling was carried out by means of Simple Random Sampling as many as 30 samples.The research results showed that the perception of lowland rice farmers on agricultural technology in Tatengesan Village, Pusomaen District, Southeast Minahasa Regency was in the good category. This is proven based on the results of research with a perception index of 74.73 percent which was classified as the good category.